Microstructure and tribological properties of NiCrAlY-Mo-Ag composite by vacuum hot-press sintering. (September 2017) - Li, Bo; Gao, Yimin; Han, Minmin; Guo, Hongjian; Wang, Wenzhen; Jia, Junhong
Abstract: The NiCrAlY-Mo-Ag composite was fabricated by vacuum hot-pressing sintering. The friction and wear behaviour of the composite were investigated from room temperature to 900 °C. Furthermore, the wear mechanism was studied over this wide range of temperatures. At the same time, the compressive properties of the composite were researched. The composition and microstructure of the composite were analyzed by X-ray diffraction (XRD) and scanning election microscopy (SEM). At 700 °C and 900 °C, the tribo-chemical reaction occurred on the worn surface and formed a high-temperature tribo-layer based on NiO and silver molybdates, which could effectively reduce the friction coefficient and wear rate of the composite. The existence of broken particles and the pullout of hard phase particles were seen on the fracture surface of the composite, which were determined by the interfacial bonding strength. Highlights: The HP composite has dense and homegeneous structure as compared to the APS coating. The HP composite has excellent tribological properties as compared to the APS coating. The fracture surface of the HP composite exists the broken particle and pullout of hard phase particles.